Чинники впливу на депозитну політику банків України - Матвійчук, Наталія Миколаївна; Жигар, Наталія Михайлівна; Петриняк, Андрій Ярославович (Видавничий дім "Гельветика", 2024)
У статті виокремлено та проаналізовано основні зовнішні та внутрішні чинники, що впливають на форму вання депозитної політики українських банків. Зовнішні чинники не підлягають регулюванню банком. Внутрішні чинники виникають всередині банку і підлягають коригуванню. Зовнішні чинники впливу: політична ситуація в країні, стан економіки та соціального середовища, соціальні настрої населення, стан фінансового ринку, доходи населення, регуляторна політика Мінфіну та НБУ, особливості системи гарантування вкладів, податкова політика щодо депозитів, рівень довіри до банків та стан фінансової грамотності населення. Основними внутрішніми чинниками впливу є: рівень менеджменту банку, різноманітність банківських послуг та прогресивність банківських технологій, прибутковість та ліквідність банку, рівень стабільності депозитів, цінова політика в сфері залучення коштів, ефективність розміщення залучених коштів.

The deposit policy of Ukrainian banks today is formed in an extremely dynamic and difficult-to-predict environment with many influencing factors, which requires special attention of bank management. The article aims to study the external and internal factors influencing the formation of the deposit policy of Ukrainian banks in modern conditions. The main external and internal factors influencing the deposit policy of Ukrainian banks are identified and analyzed in the article. The bank cannot regulate external factors, it must predict them and adjust the deposit policy accordingly. Internal factors arise within the bank and are subject to adjustment. It has been established that the external factors of influence are: the political situation in the country, the state of the economy and social environment, the social attitudes of the population, the state of the financial market, the income of the population, the regulatory policy of the Ministry of Finance and the NBU, the peculiarities of the deposit guarantee system, the tax policy regarding deposits, the level of trust in banks and the state of financial literacy of the population. It was determined that the main internal factors of influence are: the level of bank management, the variety of banking services and the progressiveness of banking technologies, the profitability and liquidity of the bank, the level of stability of deposits, the price policy in the field of raising funds, the efficiency of the placement of raised funds. The mechanism of the influence of the main factors on the level of deposit rates of Ukrainian banks, the dynamics of the volume of deposits and the structure of the deposit portfolio of banks in 2020–2023 is substantiated. The practical value of the article lies in the formation of an understanding of all the factors affecting the deposit policy of banks and, in view of this, forecasting the main trends in the deposit market
Keywords: депозит; банк; депозитна політика; НБУ; монетарна політика; облікова ставка; інфляція; обов'язкові резерви; G 21; 336.71